The Influence of Company Growth, Corporate Governance, Capital Structure, and Profitability on the Value of Infrastructure Sector Companies Listed on the BEI for the 2017-2021 Period - Auliani, Nur Andini; Ahmad, Gatot Nazir; Kurnianti, Destria (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2024)
This research aims to analyse the factors that influence the value of infrastructure sector companies listed on the Indonesia Stock Exchange (BEI) in 2017-2021. This research uses an associative causal approach with quantitative analysis techniques using panel data regression methods. The data regression test is divided into three phases, namely before the pandemic from 2017-2019, during the pandemic from 2020-2021, and the overall research period from 2017-2021. The significance levels used to test this research are 1%, 5%, and 10%. The total sample is 28 infrastructure sector companies on the IDX. Tests on company value using the PBV proxy show mixed results. In model 1, namely before the pandemic, the influence of corporate governance, capital structure, and profitability were significantly positive on company value. Then, the control variable company age has a significant negative effect on company value. Next, in model 2, namely during the COVID-19 pandemic, the results show that corporate governance has a significant positive effect on company value. Meanwhile, the influence of the control variable company age has a significant negative effect on company value. Furthermore, model 3, namely during the entire research period, shows that the capital structure and profitability variables have a significant positive effect on company value. Then, the influence of the control variable on company value, namely company age, has a significant negative effect. Based on test robustness that has been done, it is known that the selection of profitability variables is proxied by Return on Assets has a strong influence. The effect of profitability on firm value as proxied by PBV and Tobin's Q has the same results.